Pengaruh Dana Pihak Ketiga, Biaya Operasional Pendapatan Operasional, dan Loan to Deposit Ratio Terhadap Profitabilitas Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018 - Efritati Hasibuan; Hanny Theresya; Lidya Fronika Lumban Gaol; Wilsa Road Bettermen Sitepu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study aims to find and examine how the effect of DPK, BOPO, and LDR on Profitability in the Banking Sector Listed on the IDX 2016-2018. Descriptive method is used in this research method and also the quantitative approach, and this type of quantitative research aims to examine the population and sample. And to examine the population and the sample the researcher used a purposive sampling technique. Population of 44 companies with a sample of 17 companies from 2016-2018. Data collection techniques consist of reviewing documentation data and secondary data sources from the IDX financial statements for the 2016- 2018 period. This research has been tested in multiple linear regression studies. Existing data will be tested with the Classical Assumption Test. Hypothesis testing and classical assumption tests use the T and F tests in SPSS. DPK has a positive and significant effect on profitability partially, BOPO has no effect and is not significant to partially Profitability, LDR has a partial and significant effect on Profitability in the Banking Sector Listed on the Indonesia Stock Exchange